Growth and Physiological Performance of Aerobic and Lowland Rice as Affected by Water Stress at Selected Growth Stages - Nadzariah Kamarul Zaman; Mohd Yusoff Abdullah; Sariam Othman; Nadzirah Kamarul Zaman (Rice Science, 2018)
Aerobic rice technology is still new in Malaysia, and information regarding MARDI Aerob 1 (MA1), the first local aerobic rice variety, is still lacking. Therefore, comparative studies were carried out to determine the physiological performance of aerobic rice variety MA1 and lowland rice variety MR253 under water stress given at the panicle initiation, flowering and ripening stages. This experiment was arranged in a randomized complete block design. Stomatal conductance (gs), chlorophyll a fluorescence (Fv/Fm), leaf relative water content (leaf RWC), and soil moisture content (SMC) as well as yield component parameters such as panicle number, grain yield and 100-grain weight were measured. Results revealed that gs and leaf RWC for both varieties decreased with depletion of SMC. The correlation study between the physiological parameters and SMC indicated that Fv/Fm was not affected by water stress, regardless of varieties. The yield components (panicle number, grain yield and 100-grain weight) for both varieties greatly decreased when water stress was imposed at the panicle initiation stage. This study showed that the panicle initiation period was the most sensitive stage to water stress that contributed to a substantial reduction in yield for both varieties. Under the aerobic condition (control), MR253 produced higher panicle number, 100-grain weight and yield than MA1. Although MR253 is bred for lowland, it is well adapted to aerobic condition.